Some improvements of wind speed Markov chain modeling. (September 2015) - Tang, Jie; Brouste, Alexandre; Tsui, Kwok Leung
Abstract: In this study, the traditional Markov chain method for wind speed modeling is analyzed and two improvements are introduced. New states categorization step and wind speeds simulation step are presented. They both take advantage of the empirical cumulative distribution function of the wind speed time series. Performances of the new method are tested in terms of modeling and short-term forecasting. The results suggest that this method overperforms the traditional one for modeling. Highlights: A new state categorization method is introduced to the Markov chain method. A new method to generate synthetic wind speeds is introduced to the Markov chain method. Forecasting performances of two modelling methods' are compared.